200k views
1 vote
The product of a binomial and a trinomial is x 3 + 3 x 2 − x + 2 x 2 + 6 x − 2. Which expression is equivalent to this product after it has been fully simplified? A=x3 + 5x2 + 5x – 2 B=x3 + 2x2 + 8x – 2 C=x3 + 11x2 – 2 D=x3 + 10x2 – 2

User Bill Dami
by
4.9k points

2 Answers

3 votes

Answer:

A

Explanation:

User Hawili
by
5.0k points
1 vote

Answer:


A=x^(3)+5x^(2)+5x-2

Explanation:

Adding the similar terms, that is the terms that have the same power in the varible.


x^(3) \\ +3x^(2) + 2x^(2) \\-x+6x\\-2

User Dmytro Ivanov
by
5.5k points